2021
DOI: 10.3390/mi12080972
|View full text |Cite
|
Sign up to set email alerts
|

Intracortical Microelectrode Array Unit Yield under Chronic Conditions: A Comparative Evaluation

Abstract: While microelectrode arrays (MEAs) offer the promise of elucidating functional neural circuitry and serve as the basis for a cortical neuroprosthesis, the challenge of designing and demonstrating chronically reliable technology remains. Numerous studies report “chronic” data but the actual time spans and performance measures corresponding to the experimental work vary. In this study, we reviewed the experimental durations that constitute chronic studies across a range of MEA types and animal species to gain an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 191 publications
(119 reference statements)
2
22
0
Order By: Relevance
“…Our goal was to quantify the neurophysiological differences in single unit activity in the motor cortex of rats between conditions under anesthesia versus awake and freely behaving using intracortical silicon MEAs. We considered an early chronic period [ 7 ] post-implantation of MEAs and observed that the AEY was similar from these animals across the anesthetized and awake conditions. Furthermore, we noted a significantly higher SNR and lower noise levels for anesthetized recordings as compared to awake recordings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our goal was to quantify the neurophysiological differences in single unit activity in the motor cortex of rats between conditions under anesthesia versus awake and freely behaving using intracortical silicon MEAs. We considered an early chronic period [ 7 ] post-implantation of MEAs and observed that the AEY was similar from these animals across the anesthetized and awake conditions. Furthermore, we noted a significantly higher SNR and lower noise levels for anesthetized recordings as compared to awake recordings.…”
Section: Discussionmentioning
confidence: 99%
“…The trauma from insertion as well as the continued presence of these devices elicit a foreign body response, resulting in macrophage and microglia activation, glial encapsulation, neuronal dieback, a breakdown of the blood–brain barrier [ 3 , 4 ], and oxidative stress [ 5 ] in the vicinity of the probe. Resulting degradation to the probe and adverse effects on the tissue cause an eventual decrease in long-term recording performance and reliability [ 4 , 6 , 7 ]. There are many approaches to mitigate the detrimental effects leading to MEA failure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Success of silicon-based microneedle electrodes can also be found for human electrophysiology research. [31,32] First, we used the device layer to fabricate the conductive silicon microneedle array with a series of customized deep reactive ion etching (DRIE) steps (Figure 2b-d) to create a sharp tip and several angles on the silicon microneedles, which we further describe in Figure S1, Supporting Information. The microneedle array was embedded partially in polydimethylsiloxane (PDMS).…”
Section: Mina Design and Fabricationmentioning
confidence: 99%
“…Each electrode had an independent mechanical coupling to a low-modulus substrate. The design of microneedle nerve array (MINA) device was inspired by the success of the Utah array [30][31][32] and carbon fiber [9,26] particularly for the demonstrated mechanical robustness. Penetrating electrode arrays offer a larger spatial coverage of a small nerve than one transverse thin film array.…”
Section: Introductionmentioning
confidence: 99%